2017
DOI: 10.1136/bmjopen-2017-017536
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Australians with respiratory disease living in the community with experience of self-managing through an emergency department ‘near miss’ for breathlessness: a strengths-based qualitative study

Abstract: ObjectivesBreathlessness ‘crises’ in people with chronic respiratory conditions are a common precipitant for emergency department (ED) presentations, many of which might be avoided through improved self-management and support. This study sought insights from people with experience of ED ‘near misses’ where they considered going to the ED but successfully self-managed instead.Design and methodsA qualitative approach was used with a phenomenological orientation. Participants were eligible if they reported breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 46 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…Timely and accurate identification of the impact of the symptom, and routine evaluation over the course of the illness, will facilitate more targeted self-management options for people who live with this symptom. 11,21,35 At the health system level, systematic screening and assessment may help to reduce the unplanned use of primary and secondary health care, including acute-on-chronic breathlessness presentations to emergency departments and hospital admissions. 10,[36][37][38][39] Future therapeutic interventions should aim to improve people's ability to perform activities both for basic self-care, and to enrich life, reduce/prevent social isolation, and its impact on mental well-being; and to stop and/or reverse deconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely and accurate identification of the impact of the symptom, and routine evaluation over the course of the illness, will facilitate more targeted self-management options for people who live with this symptom. 11,21,35 At the health system level, systematic screening and assessment may help to reduce the unplanned use of primary and secondary health care, including acute-on-chronic breathlessness presentations to emergency departments and hospital admissions. 10,[36][37][38][39] Future therapeutic interventions should aim to improve people's ability to perform activities both for basic self-care, and to enrich life, reduce/prevent social isolation, and its impact on mental well-being; and to stop and/or reverse deconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…9 Identifying the impact of chronic breathlessness on people's activities in the general population is pivotal for designing and promoting self-management and other symptom treatment strategies, and to help ultimately reduce unplanned health service utilization. 10,11 The association between chronic breathlessness and impaired function has been demonstrated, but the range of the activities forgone as chronic breathlessness worsens has not been systematically captured at a population level. Describing any impact on populations (recruited independently of people's contact with health services) is important, given that chronic breathlessness remains largely invisible to health systems.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the original study was to explore the ED‐related decision‐making from the perspective of people with experience of successfully self‐managing through a breathlessness crisis. Detailed methods for this study have been reported in accordance with the Consolidated Criteria for Reporting Qualitative Research (COREQ) (Tong, Sainsbury, & Craig, ) in an open access journal (Luckett et al, ). The current paper focusses on a secondary analysis of coping moderators.…”
Section: The Studymentioning
confidence: 99%
“…The Transactional Model of Stress and Coping (‘Transactional Model’) (Lazarus & Cohen, ) suggests that people's capacity to cope with a stressor such as chronic illness is affected by their subjective appraisal of the stressor and self‐efficacy in controlling it using the means at their disposal. When applied to patient experiences of breathlessness crises, the Transactional Model has suggested that the most important factors in avoiding ED presentation are perceived control over the crisis and self‐efficacy in managing the affective dimension of experience (Luckett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a rural Canadian study, long-term relationships with general practitioners (GPs), community support and personalised care helped to overcome issues of restricted specialist access in COPD care 14. In the Australian context, a study found that self-monitoring of symptoms and support from health professionals assisted patients to manage breathing difficulties and avoid emergency department presentations 15. Social inclusion and a sense of belonging in COPD has been shown to influence a person’s experience of living with COPD 16 17.…”
Section: Introductionmentioning
confidence: 99%